1966
DOI: 10.1126/science.153.3740.1116
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in vitro: Effects of Sephadex Fractions of Chick Embryo Extract

Abstract: Chicken embryo extract has been fractionated into high-and low-molecular-weight components on Sephadex G-25. Media supplemented with the low-molecular-weight fraction (L) support full differentiation in clones of cartilage and of pigmented retina cells from chicken embryos. Growth rates of such cultures in L-supplemented media are greater than in media without embryo extract, and plating efficiencies are higher than in media with or without whole embryo extract. The high-molecular-weight fraction (H) in low co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0

Year Published

1967
1967
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…25 By contrast, chondrocytes cultured in atelocollagen gel maintained the chondrocyte phenotype and synthesised a chondroitin-6-sulphate-rich matrix. In addition, Coon and Cahn 35 reported that dedifferentiated chondrocytes, during four successive clonal passages in monolayer culture, re-expressed chondrocyte phenotypes when they were in contact with normal chondrocytes or were in the presence of unknown highmolecular-weight molecules. Dedifferentiated chondrocytes only re-express the differentiated chondrocyte phenotype after a limited number of passages.…”
Section: Discussionmentioning
confidence: 99%
“…25 By contrast, chondrocytes cultured in atelocollagen gel maintained the chondrocyte phenotype and synthesised a chondroitin-6-sulphate-rich matrix. In addition, Coon and Cahn 35 reported that dedifferentiated chondrocytes, during four successive clonal passages in monolayer culture, re-expressed chondrocyte phenotypes when they were in contact with normal chondrocytes or were in the presence of unknown highmolecular-weight molecules. Dedifferentiated chondrocytes only re-express the differentiated chondrocyte phenotype after a limited number of passages.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several tissues (e.g., pancreas, mammary gland) exhibit a pattern of growth in which a stem cell line which undergoes rapid divisions throws off daughter cells which only express their differentiation after divisions have stopped or slowed considerably. While this may be the case in muscle and many glandular tissues, it may not be the rule in tissues such as pigmented retina, cartilage, and cardiac muscle.…”
mentioning
confidence: 99%
“…This was supported by Elmer (1969) with other American Creeper chick embryos. In addition, it has been reported by Coon and Cahn (1966) that two Sephadex fractions of chick embryo extract had different effects on cultures of chondrocytes : the low molecular fraction had an effect in promoting the differentiation and the high molecular fraction had an effect in suppressing the differentiation. Experiments along this line in which Creeper chick embryo extract may be tested for its activity in the differentiation and proliferation of chondrocytes remain to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have studied cytodiff erentiation by using chondrocytes (Holtzer et al 1960;Kuroda 1964aKuroda , 1964bCoon and Cahn 1966;Cahn and Lasher 1967).…”
mentioning
confidence: 99%